Rhetoric versus reality : what we know and what we need to know about vouchers and charter schools - Gill, Brian P., 1968- (Rand Education, 2001)
Widespread dissatisfaction with our nation's public education system has led to proposals for a variety of reforms to improve educational outcomes. One highly controversial proposal would provide financial grants, or "vouchers," for use at any public or private school. Another, more politically popular proposal would establish "charter" schools, funded by public money and approved by a public agency but operating outside the traditional system of public-school governance. Both vouchers and charters promote educational choice, market accountability, and schools that are autonomously operated by non-government organizations. This book seeks to identify and articulate the full range of empirical questions that must be answered to fully assess the wisdom of policies that promote either of these alternatives. Eschewing the polemics that characterize both sides of the debate on school choice, the authors provide a comprehensive assessment of what is known about the effects of vouchers and charters in terms of five important outcomes: academic achievement, family choice, equitable access, racial/ethnic integration, and civic socialization. The book discusses the important empirical questions that are as yet unresolved and considers the prospects for answering them in the future. Finally, it explores the details of the design of voucher and charter policies, concluding with recommendations for policymakers who are considering their enactment